Horka st. 1. Przyczynek do badań archeologicznych nad okresem rzymskim i wędrówek ludów na północnych skrajach Polesia Prypeckiego - Beliavets, Vadzim (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The article presents results of Archaeological excavations conducted in 2020 at the settlement of Horka, site 1, located at the northern end of the Pripyat Polesia. Two chronological periods and two different cultures have been distinguished at the site: the Early Roman (the Post-Zarubintsy horizon), and the Migration Period (the Prague culture). Further analysis based on data obtained from the neighbouring settlements of Jaskavičy 1 and Doŭgaje st. 6 shows that there was continuous settlement development here throughout the first half and half of the first millennium AD: the Post-Zarubintsy horizon, the Kiev and Prague cultures. The nature and rhythm of cultural change established for this micro-region, as well as specific changes in the location of sites in the landscape, correspond to the picture that characterises the cultural development of the ‘Slavic line’ throughout Eastern Europe. The data obtained confirm the hypothesis that Pripyat Polesia could have entered the zone of formation of the Prague culture.